INTERACTIVE TEACHING MATERIAL DEVELOPMENT MODEL TO IMPROVE PERSONALIZED LEARNING GENERATION - Salsabila Fitriyani; Siti Aulia Sintia; Muhammad Cikal Fakhrizal (Jurnal Intelek Insan Cendikia, 2025)
This study was motivated by the growing need for relevant learning materials for Generation Z, who are highly tech-savvy and require interactive, flexible materials tailored to individual learning needs. The purpose of this study was to analyze effective models for developing interactive teaching materials that support personalized learning for Generation Z and to identify how these materials can improve key aspects of their learning process. The methodology used was a Systematic Literature Review (SLR) based on PRISMA guidelines, selecting articles from the ERIC, Mendeley, ScienceDirect, and PubMed databases published between 2020 and 2025. The results show that interactive teaching materials developed through valid and structured models such as ADDIE have been proven to increase learning engagement, conceptual understanding, learning independence, and critical thinking skills. In addition, personalized learning is more effective when supported by digital technology, artificial intelligence, and learning analytics that enable the adjustment of learning paths according to individual characteristics. These findings confirm that interactive teaching materials have great potential to create more effective, adaptive learning that meets the needs of Generation Z.